Communication and behavior in organizations: An experiment - Piotr Evdokimov; Umberto Garfagnini (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
We design a laboratory experiment to study behavior in a multidivisional organization facing a trade-off between coordinating its decisions across the divisions and meeting division-specific needs that are known only to the division managers. The managers communicate their private information through cheap talk. While the results show close to optimal communication, we also find systematic deviations from optimal behavior in how the communicated information is used. Specifically, subjects' decisions show worse than predicted adaptation to the needs of the divisions in decentralized organizations and worse than predicted coordination in centralized organizations. We show that the observed deviations disappear when uncertainty about the divisions' local needs is removed and discuss the possible underlying mechanisms.
Keywords: C70; D03; C92; 330; communication; coordination; decentralization; experiment